2013
DOI: 10.1007/s12288-013-0308-6
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Antibody Titre and Development of Additional Red Cell Alloantibodies Following Intrauterine Transfusion

Abstract: Intrauterine blood transfusion is the mainstay of managing foetuses with severe anemia. It may however result in fetomaternal hemorrhage, which in cases of Rh isoimmunisation may increase the severity of the disease by enhancing the maternal immunological response to fetal antigens. This study was conducted to determine the frequency, specificity and origin of additional red cell antibodies which developed after IUT. The change in the titre of allo anti-D following IUT was also determined. Antibody detection a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…Among the benign disorders, Dubey et al [6] investigate how life-saving intra-uterine blood transfusions to Rh-negative fetuses of Rh-positive mothers may carry the risk of inducing additional maternal antibodies against fetal antigens, thereby aggravating Rhisoimmunization. Sen et al [7] similarly caution that highpressure carbon dioxide insufflation, commonly used in laparoscopic surgeries, may depress natural anticoagulant systems as well as fibrinolysis thus contributing to surgeryassociated thrombophilia.…”
mentioning
confidence: 99%
“…Among the benign disorders, Dubey et al [6] investigate how life-saving intra-uterine blood transfusions to Rh-negative fetuses of Rh-positive mothers may carry the risk of inducing additional maternal antibodies against fetal antigens, thereby aggravating Rhisoimmunization. Sen et al [7] similarly caution that highpressure carbon dioxide insufflation, commonly used in laparoscopic surgeries, may depress natural anticoagulant systems as well as fibrinolysis thus contributing to surgeryassociated thrombophilia.…”
mentioning
confidence: 99%
“…The frequency of IUTs in pregnancies with a positive anti-Rh(D) screening monitored without serological cut-off values was 11.2% (range, 4.5–58.6) in the collective cases (42/376) reported by 5 studies [ 25 , 29 , 33 , 37 , 65 ]. The number of IUTs required was only reported by 1 study with a mean of 2.4 (SD not reported) [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Antenatal treatment data were available for 24 studies (Table S 8 ) [ 24 , 25 , 29 , 30 , 33 37 , 42 , 43 , 48 , 51 , 52 , 56 , 58 63 , 65 , 71 , 80 ]. The most commonly reported antenatal treatment across these studies was IUT ( n = 9 with representative data [ 25 , 29 , 33 , 36 , 37 , 56 , 59 , 60 , 65 ]; n = 3 with nonrepresentative data [ 35 , 58 , 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…The risk of alloimmunization with new antibodies following serial intrauterine transfusions has been previously documented. 18,19 Moreover, non-White patients are at higher risk for having Rh(D) variants, which requires genotyping and was not performed in this study. 20 However, our finding that anti-C and anti-Jk (a) were the most common antibodies newly detected on subsequent prenatal screens was likely due to an anamnestic response 21 following the first IUT.…”
Section: Discussionmentioning
confidence: 99%
“…We also found that women in our IUT cohort were more likely to have “new” antibodies identified during the current pregnancy if they received a higher number of IUTs. The risk of alloimmunization with new antibodies following serial intrauterine transfusions has been previously documented 18, 19 . Moreover, non‐White patients are at higher risk for having Rh(D) variants, which requires genotyping and was not performed in this study 20 .…”
Section: Discussionmentioning
confidence: 99%